PENGARUH PENDEKATAN PERSUASIF, PENDEKATAN FORMAL DAN IKLIM ORGANISASIONAL TERHADAP KEDISIPLINAN KERJA PEGAWAI INSPEKTORAT KABUPATEN BIMA - Mawar Hidayanti Sunarto; Amir Tengku Ramly; Made Yudhi Setiani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Maximum employee discipline must be a concern for organizational leaders. Through a persuasive approach influencing attitudes, beliefs, and behavior as an effort to increase one's awareness and willingness to obey all applicable regulations. The provision of punishment, such as a warning or suspension, is referred to as a disciplinary action. In addition, a conducive and comfortable work climate will create enthusiasm for employees to work, improve performance and work discipline in every job. The purpose of this study was to determine the effect of a persuasive approach, a formal approach, and an organizational climate on the work discipline of the Bima Regency Inspectorate's employees. This study uses a quantitative approach with a survey method. The population is all civil servants in the Bima Regency Inspectorate, totaling 83 employees. In the comparison, the sampling technique is proportional random sampling with the number of samples determined as many as 65 employees. The data collection technique is a questionnaire that has been tested for validity and reliability. Data analysis is a lot of regression analysis through the help of SPSS program. The results of the study revealed that (1) the persuasive approach had a positive and significant effect on employee work discipline at the Bima Regency Inspectorate, (2) the formal approach had a positive and significant effect on employee work discipline at the Bima Regency Inspectorate, (3) the organizational climate had a positive and significant effect on work discipline of employees at the Bima Regency Inspectorate for supervision. The results showed that partially and simultaneously, the variables of the persuasive approach, formal approach and organizational climate had a positive and significant effect on employee work discipline.